ANALYSIS OF INJURY PATTERNS ON INTER COLLEGIATE SWIMMERS OF MUMBAI UNIVERSITY - Patil, Deepika; Verma , Hemant J. (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The objective of this study was to survey the pattern of injuries on inter collegiate swimmers of Mumbai university. A descriptive survey method was implemented with 94 inter collegiate male and female swimmers those were participated in inter collegiate swimming tournaments season of 2021-2022 participated in the organized inter collegiate competition held under the Mumbai university. A researcher administered questionnaire was used to obtain information pattern of injury on Swimmers. The type of injury observed for male and female Swimmers were shoulder/upper arm, back/neck, elbow/wrist/hand/finger, knee/leg, ankle/foot, concussion, hip/thigh, chest/abdomen respectively. Conclusion particular attention should be given to swimmers making the transition into collegiate level swimming. These data also suggest that injury surveillance and potential prevention strategies should focus on the shoulder for in-pool activities and the axial spine for cross-training activities.